2021
DOI: 10.1101/2021.10.11.463877
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RSV protects bystander cells against IAV infection by triggering secretion of type I and type III interferons

Abstract: We observed the interference between two prevalent respiratory viruses, respiratory syncytial virus (RSV) and influenza A virus (IAV, H1N1), and characterized its molecular underpinnings in alveolar epithelial cells (A549). We found that RSV induces higher interferon (IFN) β production than IAV and that IFNβ priming confers higher protection against infection with IAV than with RSV. Consequently, we focused on the sequential infection scheme: RSV-then-IAV. Using the A549 WT, IFNAR1 KO, IFNLR1 KO, and IFNAR1–IF… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Interestingly, Czerkies et al (2022) have reported interference between respiratory syncytial virus (RSV) and influenza A virus H1N1 in human alveolar epithelial cells (A549). The authors of the report found that previous infection of cells with RSV does not prevent a subsequent influenza virus infection, whereas RSV indeed protects bystander cells against influenza virus infection by triggering secretion of type I and type III IFNs [83]. A similar effect in PCV2b/SwIV coinfected NPTr cells could be involved and explain the PCV2b impact on the apparent inhibition of SwIV replication.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, Czerkies et al (2022) have reported interference between respiratory syncytial virus (RSV) and influenza A virus H1N1 in human alveolar epithelial cells (A549). The authors of the report found that previous infection of cells with RSV does not prevent a subsequent influenza virus infection, whereas RSV indeed protects bystander cells against influenza virus infection by triggering secretion of type I and type III IFNs [83]. A similar effect in PCV2b/SwIV coinfected NPTr cells could be involved and explain the PCV2b impact on the apparent inhibition of SwIV replication.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, Czerkies et al (2022) have reported interference between respiratory syncytial virus (RSV) and influenza A virus H1N1 in human alveolar epithelial cells (A549). The authors of the report found that previous infection of cells with RSV does not prevent a subsequent influenza virus infection, whereas RSV indeed protects bystander cells against influenza virus infection by triggering secretion of type I and type III IFNs [ 88 ]. A similar effect in PCV2b/SwIV co-infected NPTr cells could be involved and explain the PCV2b impact on the apparent inhibition of SwIV replication.…”
Section: Discussionmentioning
confidence: 99%